Evaluation of the Effect of Different Universal Adhesives on Remineralized Enamel by Shear Bond Strength and Fe-SEM/EDX Analysis - Beyza Arslandaş Dinçtürk; Cemile Kedici Alp (Journal of Functional Biomaterials)
The aim of this study is to evaluate the shear bond strength of different universal adhesives applied to intact, demineralized, and remineralized enamel surfaces with total-etch and self-etch modes and to examine the effect of universal adhesives on the Ca/P mineral atomic and mass ratios of these enamel with FE-SEM/EDX (Field Emission Scanning Electron Microscopy with Energy Dispersive X-Ray Spectroscopy) analysis. For this study, 264 bovine incisors were used. Samples in the demineralized and remineralized groups were kept in demineralization solution at 37 °C for 96 h to make an artificial initial carious lesion. After demineralization, half of the demineralized samples were remineralized with MI Paste Plus. For shear bond strength (n = 144) and FE-SEM/EDX analysis (n = 120), G-Premio Bond and Clearfil S3 Bond Universal were applied on enamel surfaces with total-etch and self-etch modes, and bond strength samples were restored with resin composite. All samples were tested. The results were evaluated statistically by a three-way ANOVA test. The shear bond strength of the remineralized enamel showed high bond strength values comparable to intact enamel for universal adhesive systems. The Ca/P mineral atomic and mass ratios in remineralized enamel showed higher values than demineralized enamel, similar to intact enamel for universal adhesive systems. Initial carious lesion surfaces are unsuitable enamel surfaces for restoration. The remineralization of this surface layer before adhesive procedures may positively affect bond strength.